A Transformational Incarnation - Sijuwade, Joshua (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2023)
This article aims to provide an explication of the doctrine of the Incarnation. A ‘Transformational Model’ of the doctrine is formulated within the metaphysical and ontological framework of Jonathan Lowe (i.e. his Non-Cartesian Substance Dualism and Four-Category Ontology). Formulating this model within this specific framework will enable the doctrine of the Incarnation to be explicated in a clear and consistent manner, and the oft-raised objections against it can be answered.